Edukasi kesehatan reproduksi pada remaja di SMA Negeri 8 Makassar - Sawidi, Hasnawati; Fara, Guntur R.; Fitri, Afrina Risalya; Nurpratiwi, Vivi (JOURNAL of Public Health Concerns, 2025)
Background: Adolescent reproductive health is crucial for developing a quality generation, yet many adolescents lack information and understanding, leaving them vulnerable to sexual risks. Comprehensive, school-based reproductive education has been proven effective in increasing awareness and healthy behaviors. In response, a university held an educational program at SMA Negeri 8 Makassar to equip adolescents with the knowledge and skills to maintain holistic reproductive health. Purpose: To increase adolescent knowledge and awareness regarding reproductive health and to prevent risky behaviors that have the potential to lead to serious problems, such as unwanted pregnancy, sexually transmitted infections (STIs), and HIV/AIDS. Methods: The activity was held on Saturday, January 9, 2025, from 8:00 a.m. to 12:00 p.m. at SMA Negeri 8 Makassar. Twenty-six participants from grade XII participated. This activity used a participatory learning approach in reproductive health education, including interactive lectures, focus group discussions, and communication simulations. Evaluation was carried out through pre- and post-tests to assess the increase in participants' knowledge. Results: Of the 26 respondents aged 15 to 18 (mean 15.81 years; SD = 0.94), the majority were 15 years old (46.2%). Prior to the education, respondents' knowledge levels were low, with 46.1% categorized as poor. Following the educational intervention, participants' understanding improved, with 69.2% achieving good knowledge in the post-test. Conclusion: The participatory approach through interactive counseling, group discussions, and simulations created a comfortable and open learning environment, reflected in a significant increase in knowledge. Material previously considered taboo became easier to understand within the context of adolescent psychological development. This intervention highlights the need for overall program continuity; it emphasizes the importance of facilitating reproductive health education effectively by schools, families, and communities. Suggestion: Reproductive health education should be provided regularly and continuously to ensure deeper understanding and application of the material in daily life. This should be done using an interactive and participatory approach, including counseling, group discussions, and simulations. Schools and guidance counselors should be involved in providing support and a safe consultation space. Keywords: Adolescents; Education; Reproductive Health Pendahuluan: Kesehatan reproduksi remaja sangat penting bagi pembangunan generasi berkualitas, namun masih banyak remaja yang kurang informasi dan pemahaman, sehingga rentan terhadap risiko seksual. Pendidikan reproduksi yang komprehensif dan berbasis sekolah terbukti efektif meningkatkan kesadaran dan perilaku sehat. Sebagai respons, perguruan tinggi mengadakan edukasi di SMA Negeri 8 Makassar untuk membekali remaja dengan pengetahuan dan keterampilan menjaga kesehatan reproduksi secara holistik. Tujuan: Meningkatkan pengetahuan dan kesadaran remaja mengenai kesehatan reproduksi serta mencegah perilaku berisiko yang berpotensi menimbulkan masalah serius, seperti kehamilan tidak diinginkan, penyakit menular seksual (PMS), dan HIV/AIDS. Metode: Kegiatan dilaksanakan pada hari Sabtu, 9 Januari 2025, mulai pukul 08.00 hingga 12.00 di SMA Negeri 8 Makassar, peserta dari kelas XII sebanyak 26 orang. Pelaksanaan kegiatan ini menggunakan pendekatan participatory learning dalam edukasi kesehatan reproduksi, mencakup ceramah interaktif, focus group discussion, dan simulasi komunikasi, dengan evaluasi melalui pre-test dan post-test untuk menilai peningkatan pengetahuan peserta. Hasil: Dari 26 responden yang berusia antara 15 hingga 18 tahun (rata-rata 15.81 tahun; SD = 0.94), sebagian besar berusia 15 tahun (46.2%). Sebelum diberikan edukasi, tingkat pengetahuan responden tergolong rendah, dengan 46.1% berada dalam kategori kurang. Setelah dilakukan intervensi edukatif, terjadi peningkatan dalam pemahaman peserta, dimana 69.2% responden mencapai kategori pengetahuan baik pada post-test. Simpulan: Pendekatan partisipatif melalui penyuluhan interaktif, diskusi kelompok, dan simulasi menciptakan suasana belajar nyaman dan terbuka yang tercermin dari peningkatan pengetahuan secara signifikan. Materi yang semula dianggap tabu menjadi lebih mudah dipahami dalam konteks perkembangan psikologis remaja. Perlunya kesinambungan program secara keseluruhan, intervensi ini menegaskan pentingnya memfasilitasi edukasi kesehatan reproduksi secara serius oleh sekolah, keluarga, dan komunitas. Saran: Edukasi kesehatan reproduksi sebaiknya berkala dan berkelanjutan agar materi dapat dipahami lebih mendalam dan diterapkan dalam kehidupan sehari-hari, dengan pendekatan interaktif dan partisipatif, meliputi penyuluhan, diskusi kelompok, dan simulasi, serta melibatkan pihak sekolah dan guru bimbingan konseling untuk menyediakan dukungan dan ruang konsultasi yang aman